An innovative approach for the evaluation of prolonged disorders of consciousness using NF-L and GFAP biomarkers: a pivotal study - Coppola, L.; Mirabelli, P.; Baldi, D.; Smaldone, G.; Estraneo, A.; Soddu, A.; Grimaldi, A. M.; Mele, G.; Salvatore, Marco; Cavaliere, Carlo (Scientific reports, 2022)
Behavioral assessments during the clinical evaluation in prolonged disorders of consciousness patients could be not sufficient for a correct diagnosis and prognostication. To this aim, we used an innovative approach, involving the ultra-sensitive determination of biological markers, correlating them with imaging parameters to investigate the prolonged disorders of consciousness (pDoC).We assessed the serum concentration of neurofilament light chain(NF-L) and glial fibrillary acidic protein (GFAP) in pDoC (n = 16), and healthy controls (HC, n = 6) as well as several clinical imaging parameters such as Fractional Anisotropy (FA), Whole Brain SUV, and White Matter Hyperintensities volumes (WMH) using PET-MRI acquisition. As for differential diagnosis task, only the imaging WMH volume was able to discriminate between vegetative state/unresponsive wakefulness syndrome (VS/UWS), and minimally conscious state (MCS) patients ( p -value < 0.01), while all selected markers (both imaging and in vitro) were able to differentiate between pDoC patients and HC. At subject level, serum NF-L concentrations significantly differ according to clinical progression and consciousness recovery ( p -value < 0.01), highlighting a potential play for the longitudinal management of these patients.